Vampire Academy - Mead, Richelle (New York : Razorbill, 2007)
Two years after a horrible incident made them run away, vampire princess Lissa and her guardian-in-training Rose are found and returned to St. Vladimir's Academy, where one focuses on mastering magic, the other on physical training, while both try to avoid the perils of gossip, cliques, gruesome pranks, and sinister plots.
Bulletin of the Center for Children's Books
Booklist
VOYA (Voice of Youth Advocates Magazine)
Popular Paperbacks for Young Adults